Correlation of JMA instrumental seismic intensity with strong motion parameters. - Karim, Kazi (Earthquake engineering & structural dynamics.)
The Japan Meteorological Agency (JMA) seismic intensity (IJMA) has been used as a measure of strong shaking for many years in Japan, and it necessitates to know the correlation between the JMA seismic intensity and other strong motion indices, e.g. Peak Ground Acceleration (PGA), Peak Ground Velocity (PGV), and Spectrum Intensity (SI). In this study, two strong motion data sets were selected; in which, the first set consists of 879 three components non-liquefied records selected from 13 major earthquake events that occured in Japan, the United States and Taiwan, and the second set consists of 17 liquefied records selected from 7 major earthquake events that occured in Japan and the United States. The JMA seismic intensity and other ground motion indices were calculated using the selected data sets. The relationships between the JMA seismic intensity and PGA, PGV and SI were then derived performing a two stage linear regression analysis. Results from the analysis show that the JMA instrumental seismic intensity shows higher correlation with SI than PGA or PGV, and it shows the highest correlation with the parameters such as the combination of PGA and SI or the product of PGA and SI. The obtained relationships are also compared with the ones obtained by other studies, which may be useful for the disaster management agencies in Japan and deployment of new SI sensors that monitor both PGA and SI.